Tumor immunology and cancer immunotherapy: summary of the 2013 SITC primer. Issue 1 (14th May 2014) - Raval, Raju R; Sharabi, Andrew B; Walker, Amanda J; Drake, Charles G; Sharma, Padmanee
Abstract : Knowledge of the basic mechanisms of the immune system as it relates to cancer has been increasing rapidly. These developments have accelerated the translation of these advancements into medical breakthroughs for many cancer patients. The immune system is designed to discriminate between self and non-self, and through genetic recombination there is virtually no limit to the number of antigens it can recognize. Thus, mutational events, translocations, and other genetic abnormalities within cancer cells may be distinguished as "altered-self" and these differences may play an important role in preventing the development or progression of cancer. However, tumors may utilize a variety of mechanisms to evade the immune system as well. Cancer biologists are aiming to both better understand the relationship between tumors and the normal immune system, and to look for ways to alter the playing field for cancer immunotherapy. Summarized in this review are discussions from the 2013 SITC Primer, which focused on reviewing current knowledge and future directions of research related to tumor immunology and cancer immunotherapy, including sessions on innate immunity, adaptive immunity, therapeutic approaches (dendritic cells, adoptive T cell therapy, anti-tumor antibodies, cancer vaccines, and immune checkpoint blockade), challenges to driving an anti-tumor immune response, monitoring immune responses, and the future of immunotherapy clinical trial design.